2017
DOI: 10.1002/ejp.1034
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcranial direct current stimulation on reduction of postsurgical opioid consumption and pain in total knee arthroplasty: Double randomized clinical trial

Abstract: The data of the present study suggest that four sessions of transcranial direct current brain stimulation over motor cortex could reduce morphine consumption and pain perception during the postoperative period in total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
5
29
0
1
Order By: Relevance
“…Published data suggest that tDCS, when used as part of multimodal postoperative analgesia can result in reduced postoperative opioid use and reduced pain in patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) (Borckardt et al, 2011), total knee arthroplasty (Borckardt et al, 2013;Borckardt et al, 2017;Khedr et al, 2017b), and hallux valgus surgery (Ribeiro et al, 2017), while results for patients who underwent lumbar spine surgery are equivocal (Dubois et al, 2013;Glaser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Published data suggest that tDCS, when used as part of multimodal postoperative analgesia can result in reduced postoperative opioid use and reduced pain in patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) (Borckardt et al, 2011), total knee arthroplasty (Borckardt et al, 2013;Borckardt et al, 2017;Khedr et al, 2017b), and hallux valgus surgery (Ribeiro et al, 2017), while results for patients who underwent lumbar spine surgery are equivocal (Dubois et al, 2013;Glaser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies have shown that tDCS applied over the primary motor cortex can indirectly activate areas of the brain involved in the modulation of pain perception (Ihle et al, 2014;Yoon et al, 2014;Sankarasubramanian et al, 2017). There is also a growing body of evidence to suggest opioid systems in the midbrain are activated during tDCS (Dossantos et al, 2012(Dossantos et al, , 2014 and that patients receiving tDCS may require less opioid analgesia (Khedr et al, 2017b). The analgesic effects of tDCS have also been enhanced when used alongside conditioned pain modulation (CPM) paradigms in healthy subjects suggesting bottom-up changes in supraspinal sites may be involved (Reidler et al, 2012;Flood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pain intensity is reduced depending on the type of surgical procedure and patient population and it is measured and presented differently in different studies. Our literature search revealed seven studies utilizing tDCS for acute postoperative pain, but only three of them presented results on opioid use and pain measurement [2,4,6]. The model used in this study highlights the increased cost of pain management when pain intensity increases.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of transcranial direct current stimulation (tDCS) as an adjuvant nonpharmacological method to conventional regional or systemic analgesia for acute postoperative pain was investigated in seven studies [1][2][3][4][5][6][7]. This was a proof-of-concept clinical trial attempting to explore the impact of tDCS combined with patient controlled intravenous morphine analgesia (PCA-IV) on analgesic use and post-thoracotomy pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation